CALCULATION OF POWER WASTE IN ELECTRICAL NETWORKS - Baratov son of Laziz Suyun, Khamdamov son of Azizjon Olimjon, Jumanov Abbas Nabijonovich, Jalilov O’rinboy Abdunayimuvich (American Journals Publishing, 2023)
The quality of electricity in the territory of our republic mainly depends on current and narguz, taking into account the interaction of magnetic currents used in the control and management of currents of electric power supply networks, frequency, voltage, currents. In winter, we can use it to improve the quality of electricity. Today, the demand for electricity is increasing. On this scale, we can use it for the purpose of reducing the length of the line in order not to increase the power loss in the overhead line. If we increase the tension, we eliminate it, we need to choose the cross section of the wire in the line. the results of the study are presented.
Keywords: electric energy, currents, power dissipation, control, voltage, magnetic flux, element, Rogovsky belt - stem, retort, probability of working state, model, reliability indicators, work ability